THE ROLE OF RELIGION EDUCATION DEALING WITH RADICALISM: Madrasah is a Religious-based Character Education Model - Supa'at . (Pascasarjana Universitas Wahid hasyim Semarang, 2017)
AbstractThe purpose of this paper is to elucidate and to look for efforts todeter spreading radicalism phenomena in the world. The terrorattacks have engulfed many part of the world and blamed onradical and extremist groups who have put Islam and Muslim onworld attention. Indeed the terror attacks have heightened agrowing sense of Islamophobia. And therein is the paradox! Shouldthe activities and “sin” of individual Muslim(s) or group(s) bevisited on an entire community and relegion? As a consequenceIslam is perceived as religion with a predilection to conflict, aggressionand violence, peace is the kennel of Islamic religion and one ofits significant ingredients. Many factor causing these phenomena,one of them is misunderstanding and misperception on Islamicnorm and teaching they had got. It must be wrong in the process ofnorm transferring and teaching-knowledge, and values. Educationis the rational answered and effort to prevent and deter radicalismphenomena. Compatibility of goals, matter, method of teachingwith development (especially moral development) of student willproduce internal power as a result of educational process.Madrasah as a varian of education or Islamic aducation empiriclyhas been contributed shaping moderat muslim, known now asIslam Nusantara.Keywords: madrasah; islamic education; radicalism;misperception; moderat